CONFERENCES AND SYMPOSIA : The road to the discovery of gravitational waves. (7th December 2016) - Braginsky, V B; Bilenko, I A; Vyatchanin, S P; Gorodetskii, M L; Mitrofanov, V P; Prokhorov, L G; Strigin, S E; Khalili, F Ya
Abstract: On 14 September 2015, the two detectors of the Laser Interferometer Gravitational-wave Observatory (LIGO) in the US recorded the first direct detection of gravitational waves. This paper reviews the contributions to this discovery by V B Braginsky's group at the Physics Department of Lomonosov Moscow State University.